Penerapan PBL dalam Meningkatkan Aktivitas dan Prestasi Belajar Proyek IPAS di Sekolah Menengah Kejuruan - Eko Mulyadi (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
This classroom action research was conducted with the aim of increasing active involvement in learning and the results of student achievement in the IPAS Project in class XTE1. By applying in PBL model., SMKN 3 Yogyakarta is trying to improve the quality of learning on spatial and connectivity topics. This research was conducted in two cycles, where each cycle consisted of two meetings that lasted 3 hours of lessons. Each series of activities consists of four stages, namely planning,acting, observing,and reflecting. Application of the PBL model with problem-oriented syntacs, organizing learning, mentoring, presenting work, analyzing and evaluating problem solving. Aspects of achievement are measured by pretest and posttest. The results showed that learning activities in cycle I was 36,75%, in cycle II was 45,84%, an increase of 9,09%. Achievement of learning outcomes in the first cycle obtained an average of 64,8, in the second cycle an average of 87,0 was obtained so that there was an increase of 22,2. The application of this PBL model needs to be in learning because it is be able to increase learning activities and student achievement.